Silver-based gradient distribution electric contact composite material for frame circuit breaker and preparation method thereof

By using silver-based gradient distribution electrical contact composite materials in frame circuit breakers, the bending and shedding problems of existing Ag-WC-C materials during welding are solved, and higher resistance to welding, breaking resistance and service life are achieved, and the quality consistency and material yield of the material are improved.

CN119703095APending Publication Date: 2025-03-28WENZHOU HONGFENG ELECTRICAL ALLOY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510038745.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The Ag-WC-C electrical contact materials used in existing frame circuit breakers are prone to bending and falling off caused by thermal stress differences when welded with copper parts, resulting in high contact resistance, unresistance of arc ablation, low service life, and low material yield.

Method used

The preparation method of silver-based gradient distribution electrical contact composite material is adopted. By mixing silver powder, reinforced phase powder and additive powder in different proportions, ball milling, pre-firing, molding, sintering and secondary pressing, gradient distribution composite material with low silver content in the middle section of the working layer and high silver content materials at both ends are prepared.

Benefits of technology

This method effectively improves the bonding strength between the electrical contacts and copper parts, improves the material's resistance to welding, breaking resistance and service life, and avoids the problem of reflux doping of edge layer materials, significantly improving the material's quality consistency and material yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703095A_ABST
    Figure CN119703095A_ABST
Patent Text Reader

Abstract

The invention provides a silver-based gradient distribution electric contact composite material for a frame circuit breaker and a preparation method thereof.The preparation method comprises the steps that silver powder, reinforced phase powder and additive powder are mixed according to two different preset proportions, and first mixed powder and second mixed powder are obtained, the mass percent of the silver powder in the mixed powder I is smaller than that of the silver powder in the mixed powder II; performing ball milling; pre-sintering is performed; pre-sintered mixed powder I is added to the middle section of a mold cavity of a mold, pre-sintered mixed powder II is added to the two ends of the mold cavity of the mold respectively, and compression molding is conducted; sintering is performed; pressing for the second time; re-sintering is performed; and shaping the re-sintered material to obtain the silver-based gradient distribution electric contact composite material for the frame circuit breaker. According to the method, the powder laying mode and the secondary mold pressing are combined, the problems that the long-strip-shaped electric contact material and the copper part are not firmly welded and deform and the like can be solved, the plasticity, compactness, arc ablation resistance, fusion welding resistance, breaking resistance and the like of the electric contact material are improved, and the consistency of product quality and the yield can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric contact materials, and in particular to a silver-based gradient distribution electric contact composite material for a frame circuit breaker and a preparation method thereof. Background Art

[0002] A frame-type circuit breaker is an electrical appliance used to distribute electrical energy and protect circuits and power equipment from overload, undervoltage, and short circuit. It is required to be able to conduct and disconnect current in normal circuits, and to conduct, carry a certain amount of time, and disconnect overload current in certain abnormal circuits. Its harsh application conditions place higher demands on the arc erosion resistance and other properties of the electrical contact materials in frame-type circuit breakers.

[0003] At present, the electrical contact materials used for frame circuit breakers mainly include Ag-WC-C, Ag-Ni-C, etc. For long strip or other special-shaped Ag-WC-C electrical contact materials, due to the large difference in thermal expansion coefficient between Ag-WC-C materials and copper parts, the thermal stress is large when welding with copper parts, and it is very easy for the electrical contact materials to be severely bent, not firmly bonded with copper parts, and fall off. This makes the current Ag-WC-C strip contacts have the disadvantages of high contact resistance, poor resistance to arc erosion, low service life, and low yield rate during service.

[0004] Patent CN103151186A improves the ablation resistance of the product by improving the wettability between the silver matrix and the reinforcement phase. This process has the problem of warping and deformation when preparing products with large differences in length and width, resulting in instability during service. Patent CN219457512U fine-tunes the contact performance by changing the contact structure to make it have better heat dissipation. This patent adds a protrusion to the static contact, that is, a protrusion is added to the copper part to prevent the silver contact above from moving, and an additional structure needs to be set. Patent CN114093686A obtains a silver metal oxide electrical contact material with a core layer of low-silver metal oxide and a surface layer of high-silver metal oxide by extrusion, improves the plasticity of the electrical contact material, improves the cracking of the material and the copper material, and makes it so that in the early stage of electrical contact, the actual contact area is located in the core with good resistance to fusion welding. In the later stage of electrical contact, the differences between different areas are eliminated, thereby improving the resistance to fusion welding of the overall material. However, during the extrusion process of this method, the surface material tends to flow back to the tail of the composite ingot and be mixed into the core material, resulting in poor product quality consistency and low yield rate.

[0005] The patent application publication number is CN101178981A, which discloses a silver-based tin oxide gradient electrical contact material and a preparation method. The electrical contact material is composed of a high-to-low stepped arrangement of the mass content of silver or tin oxide along the one-dimensional dimension direction. This patent adds powder in sequence and along the height direction, and then applies pressure at the highest position. The pressure transmission path may exceed 10mm, and the pressure decreases from top to bottom. When the upper part is compacted, the lower part may not be formed yet, which easily causes the material to have too large a difference in thermal expansion along the gradient direction, and then causes problems such as heat warping.

[0006] Therefore, there is an urgent need for a silver-based gradient distribution electrical contact composite material for a frame intelligent circuit breaker and a preparation method thereof to solve the above technical problems. Summary of the invention

[0007] In view of the defects in the prior art, an object of the present invention is to provide a silver-based gradient distribution electrical contact composite material for a frame circuit breaker and a preparation method thereof.

[0008] According to one aspect of the present invention, there is provided a method for preparing a silver-based gradient distribution electrical contact composite material for a frame circuit breaker, comprising:

[0009] Silver powder, reinforcing phase powder and additive powder are mixed in two different preset proportions to obtain mixed powder 1 and mixed powder 2, wherein the mass percentage of silver powder in the mixed powder 1 is less than the mass percentage of silver powder in the mixed powder 2;

[0010] ball milling the mixed powder 1 and the mixed powder 2 respectively;

[0011] The ball-milled materials are pre-burned separately;

[0012] Adding the pre-sintered mixed powder 1 to the middle section of the mold cavity, and adding the pre-sintered mixed powder 2 to both ends of the mold cavity, and then pressing and molding to obtain a gradient distribution composite green body;

[0013] Sintering the gradient distribution composite green body;

[0014] The sintered material is pressed for the second time;

[0015] Re-firing the material after the second pressing;

[0016] The re-fired material is shaped into a preset shape and size to obtain a silver-based gradient distribution electrical contact composite material for a frame circuit breaker.

[0017] Optionally, the mass percentage of silver powder in the first mixed powder is 60.0wt% to 75.0wt%, and the mass percentage of silver powder in the second mixed powder is 65.0wt% to 86.0wt%.

[0018] Optionally, silver powder, reinforcing phase powder and additive powder are mixed in two different preset proportions, wherein:

[0019] The first preset ratio refers to the mass percentage of each component: 60.0-75.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder; the second preset ratio refers to the mass percentage of each component: 65.0-86.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder.

[0020] Optionally, the mixed powder 1 and the mixed powder 2 are respectively ball-milled, wherein: wet ball milling is adopted, the ball-to-material ratio is 1 to 20, the rotation speed is 20 rpm to 200 rpm, and the ball milling time is 2 hours to 30 hours.

[0021] Optionally, the ball-milled materials are pre-fired respectively, wherein: the pre-fired treatment is carried out in a reducing atmosphere, the pre-fired temperature is 350° C. to 800° C., and the pre-fired time is 1 hour to 8 hours.

[0022] Optionally, the step of adding the pre-burned mixed powder 1 to the middle section of the mold cavity and adding the pre-burned mixed powder 2 to both ends of the mold cavity comprises:

[0023] The mixed powder one and the mixed powder two are added to the mold cavity by using a hopper mechanism, wherein the hopper mechanism includes a hopper, and two partition plates are provided in the middle of the hopper to divide the hopper into three cavities, and the bottoms of the three cavities are respectively connected to material shoes through material pipes, so that the mixed powder one and the mixed powder two are simultaneously added to different positions of the mold cavity through the three cavities.

[0024] Optionally, during the pressing and / or the second pressing, the pressure is 5T to 15T and the time is 0.1s to 5s.

[0025] Optionally, in the step of sintering the gradient distribution composite green body and / or re-firing the material after the second pressing, the sintering atmosphere is a reducing protective atmosphere, the sintering temperature is 700° C. to 950° C., and the sintering time is 0.5 hour to 10 hours.

[0026] According to another aspect of the present invention, there is provided a silver-based gradient distribution electrical contact composite material for a frame circuit breaker, which is prepared by using the above-mentioned method for preparing a silver-based gradient distribution electrical contact composite material for a frame circuit breaker. The working surface of the composite material includes a first end, a middle section and a second end along the length direction. The first end and the second end have the same silver content, and the silver content of the middle section is less than the silver content of the first end.

[0027] Optionally, the silver content of the middle section is 60.0wt% to 75.0wt%, and the silver content of the first end portion is 65.0wt% to 86.0wt%.

[0028] Optionally, a length ratio of the first end portion, the middle portion and the second end portion is (1:1:1) to (1:4:1).

[0029] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0030] 1. The method provided by the present invention is to lay mixed powders with different silver contents in the middle section and both ends of the mold cavity respectively. The middle section of the working layer of the composite blank adopts an electric contact material with low silver content, which has high breaking, high resistance to melting and welding, and high wear resistance; the two ends of the working layer adopt an electric contact material with high silver content, which has good plasticity and conductivity. The electric contact material of this organizational structure not only takes advantage of the good plasticity of the materials at both ends of the electric contact, so that it is not easy to bend and deform due to heat when welded with the copper parts, effectively improving the problem of the electric contact and the copper parts not being firmly combined or even falling off during service, thereby greatly improving the service life of the electric contact product; and taking advantage of the excellent anti-melting and anti-breaking performance of the middle section material, in the initial stage of electrical contact, it mainly acts on the low silver content material in the middle section. By combining the advantages of the above two materials, the overall anti-melting performance, anti-breaking ability and service life of the frame circuit breaker electric contact product can be improved.

[0031] 2. The present invention uses a secondary pressing method to make the density of the electrical contact material significantly higher than that of conventional powder pressing products, and the material has a lower resistivity and is more resistant to mechanical wear, thereby making the electrical contact more resistant to arc erosion. In addition, the present invention adopts a method of simultaneously laying two different powders in different areas of the mold cavity, avoiding the problem of backflow and doping of the edge layer material caused by the extrusion method in the prior art (such as CN114093686A), and significantly improving the quality consistency and yield rate of the material. The preparation method of the present invention is simple to operate and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0033] Figure 1 Schematic diagram of the process of preparing a silver-based gradient distribution electrical contact material in one embodiment of the present invention.

[0034] Figure 2 It is a structural schematic diagram of a hopper mechanism in one embodiment of the present invention;

[0035] Figure 2 Middle: 1 is the hopper, 2 is the material pipe, 3 is the material shoe, and 4 is the partition;

[0036] Figure 3 A schematic diagram of the connection between an electrical contact and a copper member in one embodiment of the present invention;

[0037] Figure 3 Middle: A is the copper part, B is the silver coating, C is the working layer, and D is the working surface. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] Reference Figure 1 As shown in the flow diagram, a method for preparing a silver-based gradient distribution electrical contact composite material for a frame circuit breaker provided by an embodiment of the present invention comprises the following steps:

[0040] S1, powder mixing: silver powder, reinforcing phase powder and additive powder are mixed in two different preset proportions to obtain mixed powder 1 and mixed powder 2, wherein the mass percentage of silver powder in the mixed powder 1 is less than the mass percentage of silver powder in the mixed powder 2;

[0041] S2, ball milling: ball milling the mixed powder 1 and the mixed powder 2 respectively;

[0042] S3, pre-burning: pre-burn the ball-milled materials separately;

[0043] S4, molding: adding the pre-sintered mixed powder 1 to the middle section of the mold cavity, adding the pre-sintered mixed powder 2 to both ends, and then pressing and molding to obtain a gradient distribution composite body;

[0044] S5, sintering: sintering the gradient distribution composite body;

[0045] S6, re-pressing: pressing the sintered material for the second time;

[0046] S7, re-firing: re-firing the material after the second pressing;

[0047] S8. Shaping: Shaping the re-fired material into a preset shape and size to obtain a silver-based gradient distribution electrical contact composite material for a frame circuit breaker.

[0048] In some embodiments, in step S1, the mass percentage of silver powder in mixed powder one is 60.0wt% to 75.0wt%, which is mainly used to improve the material's resistance to welding and high breaking performance; the mass percentage of silver powder in mixed powder two is 65.0wt% to 86.0wt%, which is mainly used to improve the material's plasticity and conductivity, thereby regulating the comprehensive electrical properties of the material.

[0049] In order to adjust the comprehensive electrical properties of the material, the first preset ratio refers to the mass percentage of each component: 60.0-75.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder, so as to improve the material's resistance to welding and high breaking performance; specifically, the silver powder, reinforcing phase powder and additive powder are placed in a powder mixer according to the first preset ratio for mixing, and the mixing time is 1 hour to 30 hours to obtain a mixed powder with a low silver content. The second preset ratio refers to the mass percentage of each component: 65.0-86.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder, so as to improve the plasticity and conductivity of the material; specifically, the silver powder, reinforcing phase powder and additive powder are placed in a powder mixer according to the second preset ratio for mixing, and the mixing time is 1 hour to 30 hours to obtain a mixed powder with a high silver content.

[0050] In some embodiments, the silver layer of the electrical contact material is made of pure silver or silver nickel; the reinforcing phase powder is any one of WC, Ni and W, which can increase the resistance of the electrical contact material to welding and improve the breaking capacity of the electrical contact; the additive powder includes any one or more powders of graphite, Zn, Cr, carbon fiber, Fe, Ti, Mo, Co, Ni, rare earth elements, W and WC, and the additive can improve the interface wettability between the reinforcing phase (WC, Ni, W, etc.) and the matrix (Ag), improve the bonding strength between WC and the silver matrix, and improve the plasticity of the material.

[0051] Through the powder mixing step and the above parameter settings, the dispersibility of the powder can be improved and the powders can be mixed evenly.

[0052] In some embodiments, in step S2, the mixed powder 1 and the mixed powder 2 are placed in a ball mill with a liquid medium, and wet ball milling is performed with a ball-to-material ratio of 1 to 20, a rotation speed of 20 rpm to 200 rpm, and a ball milling time of 2 hours to 30 hours to increase the surface activity of the powder, thereby increasing the bonding strength between the reinforcing phase and the silver matrix. Drying treatment is performed after wet ball milling.

[0053] In some embodiments, in step S3, the ball-milled mixed powders 1 and 2 are placed in a heat treatment furnace and pre-sintered in a reducing atmosphere at a temperature of 350°C to 800°C for 1 to 8 hours, thereby changing the physical and chemical properties of the powders and preparing for the densification of the powders in the subsequent process. After pre-sintering, the powders are crushed and sieved to select powders of suitable particle size, and the sieve aperture is 30 to 400 meshes.

[0054] Because the working layer material of the electrical contact contains C and W, it is not well welded with copper. In order to achieve good welding between the two, a silver layer is provided. In some embodiments, in step S4, a layer of composite powder is first pre-laid in the mold cavity, and the composite powder material is pure silver or silver nickel, etc., and then the mixed powder 1 and the mixed powder 2 are added to the mold cavity by using a hopper mechanism, such as Figure 2 As shown, the hopper mechanism includes a hopper 1, and two partition plates 4 are provided in the middle of the hopper 1, which divide the hopper 1 into three cavities. The bottoms of the three cavities are connected to the material shoe 3 through the material pipe 2 respectively, and the low-silver content mixed powder 1 and the high-silver content mixed powder 2 are added to different positions of the mold cavity through the three cavities at the same time. Specifically, the pre-burned mixed powder 1 is added to the middle section of the mold cavity through the hopper, and at the same time, the pre-burned mixed powder 2 is also added to the two ends of the mold cavity through the hopper, that is, 3 parts of powder are simultaneously fed into the three cavities of the hopper 1, and the material shoe 3 drives the 3 parts of powder and fills them into the cavity of the mold, and then the material in the cavity is pressed to obtain a composite body with a gradient distribution. The above-mentioned hopper powder spreading molding method is adopted to obtain an electrical contact material with a material structure with a gradient distribution along the working surface, such as Figure 3 As shown, the silver-based gradient distribution electrical contact composite material is usually processed into an electrical contact. One surface of the electrical contact is welded to the copper part A, and the surface parallel to it is the contact working surface D. The upper layer of material along the thickness direction of the contact is called the working layer C; in the thickness direction of the contact, a thin layer of material in contact with the copper part is the silver composite layer B. The gradient distribution means that along the length direction of the working surface of the composite blank, the composite blank has three sections of different materials, among which the middle section material of the composite blank is a low-silver content mixed powder 1, and the materials at both ends of the composite blank are high-silver content mixed powder 2, preparing for subsequent processing into a gradient distributed electrical contact.

[0055] In the above-mentioned embodiment of the present invention, powder is added at the same time, and the pressure transmission path along the thickness direction of the silver point is short, generally less than 3 mm; the thermal expansion difference of the material along the long side direction is small, and problems such as warping are not easy to occur.

[0056] In the above embodiments, during the pressing and / or the second pressing process, the pressure is 5T to 15T and the time is 0.1s to 5s, thereby forming a dense material body without chipping.

[0057] In the above embodiment, in the step of sintering the gradient distribution composite green body and / or re-firing the material after the second pressing, the sintering atmosphere is a reducing protective atmosphere, the sintering temperature is 700°C to 950°C, and the sintering time is 0.5 hours to 10 hours. By setting the above sintering parameters, a neck connection is formed between the powders, and the pores are reduced and shrunk, thereby improving the density and conductivity of the material. In addition, the double pressing and sintering make the material density far exceed that of conventional powder pressing products, and more resistant to arc ablation.

[0058] The above embodiment of the present invention, after step S8, further comprises: S9, cleaning and drying, that is, first grinding, cleaning and then drying the shaped material to obtain the desired silver-based gradient distribution electrical contact material.

[0059] Ag-WC-C or Ag-Ni-C electrical contact materials with low silver content have the advantages of high breaking, high resistance to welding, and good arc wear resistance. If used alone, their plasticity is poor, and the thermal expansion coefficient is greatly different from that of copper parts, and it is not easy to combine firmly with copper parts, which leads to easy point failure; Ag-WC-C or Ag-Ni-C electrical contact materials with high silver content have the advantages of good plasticity and conductivity. If used alone, their resistance to welding and anti-breaking are relatively poor, and they are prone to sticking point failure. The above embodiment of the present invention combines the electrical contact material with low silver content and the electrical contact material with high silver content, which is conducive to providing the electrical contact material with resistance to large current ablation, resistance to welding, electrical life, and strength of bonding with copper parts. The method in the above embodiment of the present invention is easy to operate, low cost, no special requirements for equipment, and the quality consistency of the prepared electrical contact material is good, the yield rate is high, and there is no problem of backflow mixing of edge materials, so that it can meet the application requirements of electrical appliances such as frame circuit breakers.

[0060] Another embodiment of the present invention provides a silver-based gradient distribution electrical contact composite material for a frame circuit breaker, which is prepared by the above-mentioned preparation method of the silver-based gradient distribution electrical contact composite material for a frame circuit breaker. The working surface of the composite material includes a first end, a middle section and a second end along the length direction. The silver content in the first end and the second end is the same, and the silver content in the middle section is less than the silver content in the first end. The middle section of the working layer of the material is a low-silver content electrical contact material, specifically, the silver content of the middle section is 60.0wt%~75.0wt%, and the breaking capacity, anti-welding property, and arc wear resistance of the material are relatively excellent; the two ends of the material are a high-silver content electrical contact material, specifically, the silver content of the first end and the second end is 65.0wt%~86.0wt%, and the conductivity and plasticity of the material are relatively excellent.

[0061] In some embodiments, the length ratio of the first end, the middle section, and the second end is (1:1:1) to (1:4:1), and this ratio is determined based on the conductivity and anti-fusion welding requirements of the two ends and the middle section of products of different specifications, as well as welding quality requirements and other factors, so that the long contacts will not warp after welding, thereby improving the conductivity of the product, helping to reduce temperature rise, and extending its electrical life.

[0062] The silver-based gradient distribution electrical contact composite material in the embodiment of the present invention has a working layer with a gradient distribution structure along the working surface. The material density far exceeds that of conventional powder pressing products, and the material with high resistance to welding, high breaking rate and low plasticity is in the middle, and the materials with high conductivity, high plasticity and relatively low resistance to welding are at both ends. The silver-based gradient distribution composite material has the advantages of both, so that the frame circuit breaker electrical contact product made of this material has high resistance to welding, high breaking rate and longer service life.

[0063] Continue to refer to Figure 1 In a specific embodiment, a method for preparing a silver-based gradient distribution Ag67Ni30C3 / Ag64Ni32C3 / Ag67Ni30C3 electrical contact composite material for a frame intelligent circuit breaker comprises the following steps:

[0064] S2. Silver powder, nickel powder and additive powder are placed in a powder mixer according to a first preset ratio for mixing, and the mixing time is 3 hours to obtain a mixed powder with a low silver content. Silver powder, nickel powder and additive powder are placed in a powder mixer according to a second preset ratio for mixing, and the mixing time is 3 hours to obtain a mixed powder with a high silver content. The additives include graphite, Co and WC. In the first preset ratio, the weight portions of various powders are: 64.0 parts of silver powder, 3.5 parts of additive powder, and the balance is reinforcing phase powder; in the second preset ratio, the weight portions of various powders are: 67 parts of silver powder, 3.0 parts of additive powder, and the balance is reinforcing phase powder.

[0065] S2. Put the mixed powder 1 and acetone into a horizontal ball mill for wet ball milling, and then dry it after completion to obtain the mixed powder 1 after ball milling; put the mixed powder 2 and acetone into a horizontal ball mill for wet ball milling, and then dry it after completion to obtain the mixed powder 2 after ball milling; wherein the ball milling process parameters are: ball-to-material ratio of 10, rotation speed of 150 rpm, and ball milling time of 8 hours.

[0066] S3. The ball-milled mixed powders 1 and 2 are placed in a heat treatment furnace respectively, and pre-burned in a reducing atmosphere, and then crushed and sieved; wherein the pre-burning temperature is 650°C, the pre-burning atmosphere is H2, the time is 4 hours, and the sieve aperture is 200 mesh.

[0067] S4. First, a layer of AgNi10 powder is pre-laid in the mold cavity, and the pre-burned mixed powder 1 is added to the middle section of the mold cavity using a hopper. At the same time, the pre-burned mixed powder 2 is added to both ends of the mold cavity using the same hopper. Then, the material in the mold cavity is pressed at a pressure of 10T for 0.5s to obtain a gradient distributed Ag67Ni30C3 / Ag64Ni32C3 / Ag67Ni30C3 composite body, and the gradient ratio along the length direction of the working surface is 1:2:1.

[0068] S5. Sintering: The Ag67Ni30C3 / Ag64Ni32C3 / Ag67Ni30C3 composite body is sintered in a gradient distribution, with a sintering atmosphere of H2, a sintering temperature of 900°C, and a sintering time of 6 hours.

[0069] S6. The sintered material is pressed for the second time with a pressure of 12T and a time of 1s.

[0070] S7. Sinter the re-pressed material again, with the sintering atmosphere being H2, the sintering temperature being 900°C, and the sintering time being 6 hours.

[0071] S8. According to the product shape and size requirements, the re-fired materials are shaped into finished products.

[0072] S9. Grind, clean and then dry the shaped material to obtain the required Ag67Ni30C3 / Ag64Ni32C3 / Ag67Ni30C3 electrical contact material.

[0073] Taking AgNi30C3 used in conventional frame circuit breakers as a comparison, the test results of the bonding strength and electrical life test performance of the two with copper parts are shown in Table 1.

[0074] Table 1 Comparison of welding strength and electrical life test performance

[0075]

[0076] According to the performance test results in Table 1, compared with conventional frame circuit breaker electrical contact materials, the Ag67Ni30C3 / Ag64Ni32C3 / Ag67Ni30C3 electrical contact material prepared by the method in the above embodiment of the present invention has higher bonding strength and longer electrical life (i.e., service life).

[0077] In the above embodiment of the present invention, by combining powder spreading and secondary molding, the obtained silver-based gradient distribution electrical contact material combines the advantages of high silver content materials and low silver content materials, and can improve the problems of weak welding and deformation between the long strip electrical contact material and the copper parts, and improve the plasticity, density, arc ablation resistance, welding resistance and breaking resistance of the electrical contact material product, thereby extending its service life. In addition, the method in the above embodiment of the present invention avoids the problems of easy backflow of composite materials in the existing extrusion method, resulting in mixing and low yield, thereby improving the consistency of product quality and yield.

[0078] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essence of the present invention. The above preferred features can be used in any combination without conflicting with each other.

Claims

1. A method for preparing a silver-based gradient distribution electrical contact composite material for a frame circuit breaker, characterized in that: include: Silver powder, reinforcing phase powder and additive powder are mixed in two different preset proportions to obtain mixed powder 1 and mixed powder 2, wherein the mass percentage of silver powder in the mixed powder 1 is less than the mass percentage of silver powder in the mixed powder 2; ball milling the mixed powder 1 and the mixed powder 2 respectively; The ball-milled materials are pre-burned separately; Adding the pre-sintered mixed powder 1 to the middle section of the mold cavity, and adding the pre-sintered mixed powder 2 to both ends of the mold cavity, and then pressing and molding to obtain a gradient distribution composite green body; Sintering the gradient distribution composite green body; The sintered material is pressed for the second time; Re-firing the material after the second pressing; The re-fired material is shaped into a preset shape and size to obtain a silver-based gradient distribution electrical contact composite material for a frame circuit breaker.

2. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: The mass percentage of silver powder in the first mixed powder is 60.0wt% to 75.0wt%, and the mass percentage of silver powder in the second mixed powder is 65.0wt% to 86.0wt%.

3. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 2, characterized in that: Silver powder, reinforcing phase powder and additive powder are mixed in two different preset proportions, wherein: The first preset ratio refers to the mass percentage of each component: 60.0-75.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder; the second preset ratio refers to the mass percentage of each component: 65.0-86.0 parts of silver powder, 0.1-5.0 parts of additive powder, and the balance is reinforcing phase powder.

4. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: The mixed powder 1 and the mixed powder 2 are respectively ball-milled, wherein: wet ball milling is adopted, the ball-to-material ratio is 1-20, the rotation speed is 20 rpm-200 rpm, and the ball milling time is 2 hours-30 hours.

5. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: The ball-milled materials are pre-fired respectively, wherein: the pre-fired treatment is carried out in a reducing atmosphere, the pre-fired temperature is 350° C. to 800° C., and the pre-fired time is 1 hour to 8 hours.

6. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: The method of adding the pre-burned mixed powder 1 to the middle section of the mold cavity and adding the pre-burned mixed powder 2 to both ends of the mold cavity comprises: The mixed powder one and the mixed powder two are added to the mold cavity by using a hopper mechanism, wherein the hopper mechanism includes a hopper, and two partition plates are provided in the middle of the hopper to divide the hopper into three cavities, and the bottoms of the three cavities are respectively connected to material shoes through material pipes, so that the mixed powder one and the mixed powder two are simultaneously added to different positions of the mold cavity through the three cavities.

7. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: During the pressing and / or the second pressing, the pressure is 5T to 15T and the time is 0.1s to 5s.

8. The method for preparing the silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 1, characterized in that: In the step of sintering the gradient distribution composite green body and / or re-firing the material after the second pressing, the sintering atmosphere is a reducing protective atmosphere, the sintering temperature is 700° C. to 950° C., and the sintering time is 0.5 hour to 10 hours.

9. A silver-based gradient distribution electrical contact composite material for frame circuit breakers, characterized in that: The composite material is prepared by the method for preparing a silver-based gradient distribution electrical contact composite material for a frame circuit breaker according to any one of claims 1 to 8, wherein the working surface of the composite material includes a first end, a middle section and a second end along the length direction, the first end and the second end have the same silver content, and the silver content of the middle section is less than the silver content of the first end.

10. The silver-based gradient distribution electrical contact composite material for frame circuit breaker according to claim 9, characterized in that: The length ratio of the first end portion, the middle portion and the second end portion is (1:1:1) to (1:4:1).

Citation Information

Patent Citations

  • Silver-based tin oxide gradient electric contact material and preparation method thereof

    CN101178981A

  • Preparation method of composite electrical contact material for breaker

    CN103151186A

  • Method for improving material plasticity of silver metal oxide electric contact material in cold heading riveting electric contact and application of silver metal oxide electric contact material

    CN114093686A

  • Frame circuit breaker contact structure and frame circuit breaker

    CN219457512U